Development of Pop-up Book-Based Learning Media Utilizing Augmented Reality for Science Subjects - Darmawan, Puguh; Rofiki, Imam; Nugroho, Citra Maulidyah Rahmawati; Pramudya, Stansa Senia; Dewi, Vera Melinia; Hidayah, Farihatul; Maulidiawati, Tasya (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
The role of teachers in education goes beyond simply delivering teaching materials. A teacher must create an exciting and interactive learning atmosphere that captivates students' attention and encourages active participation in learning. Teachers often face challenges in creating engaging and relevant learning materials while integrating the latest technology, which can impede the achievement of learning goals and reduce the effectiveness of the teaching-learning process. A significant issue is the lack of student motivation and involvement, evident from boredom and inattention despite using various learning resources. This study aims to address this issue by developing a Pop-Up Book-based learning media utilizing Augmented Reality (AR) for science subjects in Grade V Elementary School. The research was conducted at SDN Pandanwangi 3 and followed the ADDIE development model—Analysis, Design, Development, Implementation, and Evaluation. The findings indicate that the AR-based Pop-Up Book is effective in enhancing the quality of learning. Implementing this media at SDN Pandanwangi 3 successfully motivated students, improved their understanding of the subject matter, and demonstrated high practicality according to questionnaires and learning outcomes. The final evaluation confirms that this media is valid, practical, and effective in meeting learning objectives. It is recommended that AR-based learning media, such as Pop-Up Books, be extended to other subjects and educational levels. Further research is suggested to explore the effectiveness of such media across different contexts and disciplines, ensuring broader applicability and impact in academic settings.